2021
DOI: 10.1038/s41385-021-00387-6
|View full text |Cite
|
Sign up to set email alerts
|

Murine astrovirus tropism for goblet cells and enterocytes facilitates an IFN-λ response in vivo and in enteroid cultures

Abstract: Although they globally cause viral gastroenteritis in children, astroviruses are understudied due to the lack of well-defined animal models. While murine astroviruses (muAstVs) chronically infect immunodeficient mice, a culture system and understanding of their pathogenesis is lacking. Here, we describe a platform to cultivate muAstV using air-liquid interface (ALI) cultures derived from mouse enteroids, which support apical infection and release. Chronic muAstV infection occurs predominantly in the small inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 42 publications
2
24
0
Order By: Relevance
“…Importantly, genetic modifications of HIEs have been successfully performed using CRISPR-Cas9 approaches to explore FUT2 requirements and IFN regulation of HuNoV [ 32 , 33 ]; this capacity to genetically modify HIEs is likely to be increasingly applied to enteric viral cultivation studies ( Figure 1 ). HIEs also permit efficient replication of HAstV, with HIEs derived from all intestinal segments supporting the growth of representative strains from all three clades [ 43 , 45 , 46 ]. These studies have shown that HAstV can infect multiple cell types such as goblet cells, mature enterocytes, and intestinal progenitor cells [ 43 , 45 , 46 ], and have revealed the importance of IFN-mediated antiviral responses against HAstV [ 45 ].…”
Section: In Vitro Tools To Study Human Enteric Rna Virusesmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, genetic modifications of HIEs have been successfully performed using CRISPR-Cas9 approaches to explore FUT2 requirements and IFN regulation of HuNoV [ 32 , 33 ]; this capacity to genetically modify HIEs is likely to be increasingly applied to enteric viral cultivation studies ( Figure 1 ). HIEs also permit efficient replication of HAstV, with HIEs derived from all intestinal segments supporting the growth of representative strains from all three clades [ 43 , 45 , 46 ]. These studies have shown that HAstV can infect multiple cell types such as goblet cells, mature enterocytes, and intestinal progenitor cells [ 43 , 45 , 46 ], and have revealed the importance of IFN-mediated antiviral responses against HAstV [ 45 ].…”
Section: In Vitro Tools To Study Human Enteric Rna Virusesmentioning
confidence: 99%
“…HIEs also permit efficient replication of HAstV, with HIEs derived from all intestinal segments supporting the growth of representative strains from all three clades [ 43 , 45 , 46 ]. These studies have shown that HAstV can infect multiple cell types such as goblet cells, mature enterocytes, and intestinal progenitor cells [ 43 , 45 , 46 ], and have revealed the importance of IFN-mediated antiviral responses against HAstV [ 45 ].…”
Section: In Vitro Tools To Study Human Enteric Rna Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the mechanisms of cell entry and cell tropism have not been well characterized. While some light has been shed recently on the tropism of enteric human and murine AstVs [68][69][70], the tropism for AstVs in general-especially AAstVs-remains to be determined. In this review, we summarize the current understanding of the mechanisms of transmission, mutation and recombination, cross-species transmission, and highlight areas of future research in AstV transmission.…”
Section: Introductionmentioning
confidence: 99%
“…However, murine astroviruses have not been clearly associated with a specific disease in mice, as uninfected mice excrete virus in their stool but do not develop diarrhea or systemic signs upon infection [ 53 , 54 ]. Murine astrovirus infection has been localized to goblet cells in mice leading to alterations in mucus production and subsequently, the gut microbiome, but these changes do not appear to cause a clear phenotype [ 55 , 56 ]. Interestingly, murine astroviruses may also play an important role in shaping immunity of the GI tract.…”
Section: Gastrointestinal Diseasementioning
confidence: 99%